THE RIGHT TO HIGHER EDUCATION FOR NATIONAL DEVELOPMENT AND EQUAL OPPORTUNITY IN NIGERIA: THE MAJOR CHALLENGES OF OUR TIME - Aja-Okorie, Uzoma (European Scientific Journal, ESJ, 2014)
This paper affirms that the right and equal opportunity to educationparticularly at higher levels is a policy statement which has remained at thefront burners of developmental discoveries. It observes that despite policydeclarations on educational equality, women‘s education has not completelyreceived desired attention for high level competiveness at global level. Itreveals that the journey has been tortuous. More so, in this time ofknowledge based economy and globalization gender education is generallyviewed as an indicator for meaningful development. This is especially truesince after the United Nations World Conference on Women in 1975 and thesubsequent declaration of 1975-1985, as the Decade for Women. The gainsof this decade were reinforced by the Beijing conference in 1995 and suchother conferences. The result is not totally bad but since development trendsrequire high powered skills, knowledge levels and competences, theacquisition of basic education is no longer adequate to enable both men andwomen to contribute effectively to national development. In the light of theabove it recommended that the girls/women must be encouraged to remain inschool long enough (higher institutions) to acquire the necessary skills to beable to be part of national development, government on its part mustrestructure the industrial sector to attract investors who are gender sensitiveboth in providing educational opportunities and in employment. Whilefemale drop-out rate must be checked, enrolment drive must be undertakento get more girls into schools and into higher institutions as quality educationremains the fastest and the best way to empower potential beneficiaries fornational development.